2014
DOI: 10.1007/s10803-014-2169-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Factor Structure of Parent Reported Executive Function in Autism Spectrum Disorders: The Impact of Cognitive Inflexibility

Abstract: Parents of children with autism spectrum disorders (ASD) consistently report executive functioning (EF) deficits. This study investigates the factor structure of the Behavior Rating Inventory of Executive Function (BRIEF) as reported by parents of children with ASD and typically developing children (TDC). BRIEFs for 411 children with ASD and 467 TDC were examined. Confirmatory factor analysis of a nine-factor model met thresholds for goodness-of-fit in TDC, but not in the ASD sample. We found globally elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
53
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 42 publications
14
53
1
2
Order By: Relevance
“…No single account has been able to explain the wide variety of differences that tend to co-exist in autism spectrum conditions; however, several theories have received significant empirical support. Most prominent have been those related to limitations in theory of mind (the ability to conceptualize and reason about other people’s internal states, i.e., Baron-Cohen, 1995, Kana et al, 2015), weak executive function (the ability to organize and manage one’s cognitive processes in a flexible way, i.e., Ozonoff et al 1991; Pennington and Ozonoff 1996; Granader et al 2014), and bias toward local over global coherence (the tendency to focus on details, and calculate precise relationships between those details, rather than synthesizing them intuitively into a big-picture gestalt, i.e., Happé and Frith, 2006). Baron-Cohen et al (2003) have suggested that a preference for systematizing (analyzing variables in a system to discern their underlying rules) over empathizing (intuitively inferring the internal states of others) may be fundamental to the autistic cognitive style, arguing that some of the social struggles experienced by people on the autism spectrum result from a fruitless search to find the systems that reliably predict human behavior.…”
Section: The Need For External Structure In Autism Spectrum Conditionsmentioning
confidence: 99%
“…No single account has been able to explain the wide variety of differences that tend to co-exist in autism spectrum conditions; however, several theories have received significant empirical support. Most prominent have been those related to limitations in theory of mind (the ability to conceptualize and reason about other people’s internal states, i.e., Baron-Cohen, 1995, Kana et al, 2015), weak executive function (the ability to organize and manage one’s cognitive processes in a flexible way, i.e., Ozonoff et al 1991; Pennington and Ozonoff 1996; Granader et al 2014), and bias toward local over global coherence (the tendency to focus on details, and calculate precise relationships between those details, rather than synthesizing them intuitively into a big-picture gestalt, i.e., Happé and Frith, 2006). Baron-Cohen et al (2003) have suggested that a preference for systematizing (analyzing variables in a system to discern their underlying rules) over empathizing (intuitively inferring the internal states of others) may be fundamental to the autistic cognitive style, arguing that some of the social struggles experienced by people on the autism spectrum result from a fruitless search to find the systems that reliably predict human behavior.…”
Section: The Need For External Structure In Autism Spectrum Conditionsmentioning
confidence: 99%
“…It is possible that food neophobia is one manifestation of broader anxiety or difficulties with novelty, so these individuals will also struggle with new situations in daily life (e.g., paying a store clerk for a purchased item). However, there may also be another factor, such as behavioral inflexibility, which is strongly associated with ASD (Granader, Wallace, Hardy, Yerys, et al, 2014; Yerys et al, 2009; D’Cruz et al, 2013; South et al, 2007; Reed et al, 2011) that mediates the observed correlation between food neophobia and lower daily living skills. Future research should seek to elucidate this potential connection.…”
Section: Discussionmentioning
confidence: 99%
“…Everyday executive functioning problems, which are indexed by multifactorial behavioral measures, have been consistently documented in ASD 37,38 . Additionally, we found that greater ASD social symptom severity, as measured by the ADI, was associated with thinner cortex in left ventral occipitotemporal cortex at time 2 in the group with ASD.…”
Section: Discussionmentioning
confidence: 99%